CONSTITUTIONAL AND LEGAL RECOGNITION OVER TRADITIONAL ADAT COMMUNITY WITHIN THE MULTICULTURAL COUNTRY OF INDONESIA : IS IT A GENUINE OR PSEUDO RECOGNITION? - I Nyoman Nurjaya (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
Indonesia is well known as a multicultural country in Southeast Asia in term of its ethnic,religion, racial and social stratification. It is Unity in Diversity, which is reflected in the officialmotto of the State to describe the social and cultural diversity of Indonesia. The diversity refers to a cultural configuration which reflects the National identity of Indonesia, containing cultural capital and cultural power. However, cultural diversity yields conflict that could potentially generate social disintegration due to inter-ethnic and inter-religious disputes that may result in the disintegration of Indonesia as a Nation State. In the eyes of legal anthropologists, sources of conflicts are based on discriminatory policies expressed within State’s law and legislations in line to the recognition and protection the existence of local communities, namely traditional adat communities spread out in the region. Thus, State laws enacted and enforced by the Government tend to dominate and marginalize as well as ignore the rights of the local communities particularly over access and control natural resources they based on customary adat law in the region. The paper attempts to offer an answer to the fundamental question whether the 1945 Constitution recognise and protect the traditional communities and their customary adat law by employing a legal anthropological approach with the purpose of obtaining a better understanding regarding the development of State lawin a multicultural Nation toward a more just and equitable State law of Indonesia.Keywords : Multicultural, Unity in Diversity, Conflict, Anthropological Approach